Electronic Banking In Pakistan - Khawaja, Osama Rahat (2002)
This research looks into the factors, which influences the adoption rate of Electronic Banking among the customers in Islamabad, Lahore and Karachi. The aim of this research is also to evaluate customers' perception of Electronic Banking services. Through the results obtained, recommendations are made to the bankers on the groups of customers they should target in their Internet Banking Service strategies.